PRELIMINARY STUDY ON EVOLUTION OF METALS CONTAMINANT RECORDED IN THE COASTAL SEDIMENTS OF SEMARANG WATERS - S Edi Suyarso; Tjutju Susana (JOURNAL OF COASTAL DEVELOPMENT, 2010)
The evolution of heavy metals contaminant of Cu, Zn and Hg at two main river mouths of Semarang waters have been carried out on June 2009 through sediment cores, ages determination and supporting with population and industry statistical data background. Heavy metals found at West Banjir Kanal river mouth may be associated with natural origin on the contrary the increase of metals concentration found at East Banjir Kanal river mouth is strongly correspond with population and industrial increases since industrial decades. Objective of research is to collect heavy metals contaminant concentration changed data over 30 years which have been recorded and saved in the layers of sediments in Semarang coastal waters. The goal of research is to reconstruct the evolution of contaminant concentration chronologically since industrialization decade. Method used in the research is data analysis through sediment cores supported both population and industrial statistical data.